Implementasi Kebijakan Percepatan Penurunan Stunting Pada Dinas Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Sintang - Kiranasari, Falentina; Tohardi, Ahmad; Aisyah, Siti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Stunting has been designated as a national priority issue. The target to reduce stunting by 27.6% in 2019 is expected to be 14% in 2024. Based on the 2021 Indonesian Nutrition Status (SSGI) results, Sintang District has the second largest stunting prevalence rate in West Kalimantan, which is 38.2%. So that the high prevalence of stunting can hamper efforts to improve public health and develop the quality of human resources. With the issuance of Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction, where the BKKBN is the Chief Executive, it certainly has an impact on the need for program coordination and convergence in the field. So that this automatically results in the Office of Family Planning, Women's Empowerment and Child Protection in Sintang Regency, which is an extension of the West Kalimantan Provincial BKKBN Representative, responsible for accelerating the reduction of stunting in Sintang District. Hence, the Office of Family Planning, Women's Empowerment, and Child Protection in Sintang Regency are making endeavors to expedite the reduction of stunting through diverse strategies. The aim of this research was to comprehend the execution of measures for accelerating the decline of stunting at the Sintang District Office of Family Planning, Women's Empowerment, and Child Protection, guided by the principles established by Donald Van Meter and Charles Van Meter. This research employs a case study approach, employing a qualitative descriptive research framework. The data collection techniques by way of interviews, observation and documentation/documentary studies. The results of this study are that in 2022 based on the results of the Indonesian Nutrition Status Survey (SSGI) conducted by the Ministry of Health of the Republic of Indonesia, the prevalence rate of stunting in Sintang District shows a very significant decrease. The study's outcome reveals that the execution of the strategy aimed at expediting the reduction of stunting in the context of Sintang Family Planning has been observed, Women's Empowerment and Child Protection Services has been going well and has been successful in efforts to deal with stunting by reducing the prevalence of stunting from 38.2% to 18.7%. One of the suggestions given is the need to carry out community empowerment activities in an effort to fulfill balanced nutrition for families at risk of stunting, namely families with prospective brides, pregnant women, breastfeeding mothers, toddlers and stunted toddlers, especially from underprivileged families.